PHYTOCHEMICAL EVALUATION OF ARTOCARPUS HIRSUTUS LAM. FRUIT EXTRACT: A POTENTIAL WILD ENDEMIC PLANT - P., NEHA C.; K., ABDUSSALAM A. (International Journal of Current Pharmaceutical Research, 2020)
Objective: The present study includes the qualitative and quantitative estimation of phytochemical constituents and HPTLC (High-performance thin layer chromatography) analysis of phenolic acids in the fruit extract of Artocarpus hirsutus. Methods: Qualitative and quantitative analysis of Artocarpus hirsutus methanol fruit extract using standard methods. HPTLC analysis was performed by the CAMAG HPTLC system (Switzerland) for gallic acid, caffeic acid and ferulic acid determination. Results: The Preliminary phytochemical analysis revealed the presence of phytoconstituents such as flavonoids, phenols, tannins, steroids, glycosides, alkaloids, carbohydrate and protein. The methanol fruit extract has high carbohydrate content (267±0.02 mg/g FW). And good amount of protein, phenol, flavanoid were also found. The results of mineral studies shows that elements such as potassium (1.601%) and nitrogen (1.4%) were present in higher quantity. The result showed the presence of caffeic acid within peak 7 with an Rf (Retension factor) value 0.49, ferulic acid within peak 8 with an Rf value 0.60, and gallic acid within peak 5 with an Rf value 0.25. Conclusion: The results indicated that the Artocarpus hirsutus fruit contains an appreciable amount of bioactive compounds.